Folate-mediated targeted and intracellular delivery of paclitaxel using a novel deoxycholic acid-O-carboxymethylated chitosan–folic acid micelles - Wang F (Dove Medical Press, 2012)
Feihu Wang1, Yuxuan Chen2, Dianrui Zhang1, Qiang Zhang3, Dandan Zheng1, Leilei Hao1, Yue Liu1, Cunxian Duan1, Lejiao Jia1, Guangpu Liu11Department of Pharmaceutics, College of Pharmacy, Shandong University, Jinan, People’s Republic of China; 2Department of Pharmacy, Shenzhou Hospital, Shenyang, People’s Republic of China; 3State Key Laboratory of Natural and Biomimetic Drugs, School of Pharmaceutical Sciences, Peking University, Beijing, People’s Republic of ChinaBackground: A critical disadvantage for successful chemotherapy with paclitaxel (PTX) is its nontargeting nature to cancer cells. Folic acid has been employed as a targeting ligand of various anticancer agents to increase their cellular uptake within target cells since the folate receptor is overexpressed on the surface of such tumor cells. In this study, a novel biodegradable deoxycholic acid-O-carboxymethylated chitosan–folic acid conjugate (DOMC-FA) was used to form micelles for encapsulating the anticancer drug PTX.Methods and results: The drug-loading efficiency, encapsulation efficiency, in vitro drug release and physicochemical properties of PTX-loaded micelles were investigated in detail. In vitro cell culture studies were carried out in MCF-7 cells, a human breast carcinoma cell line, with folate receptor overexpressed on its surface. An increased level of uptake of folate-conjugated micelles compared to plain micelles in MCF-7 cells was observed, and the enhanced uptake of folate-micelles mainly on account of the effective process of folate receptor-mediated endocytosis. The MTT assay, morphological changes, and apoptosis test implied that the folate-conjugated micelles enhanced the cell death by folate-mediated active internalization, and the cytotoxicity of the FA-micellar PTX (DOMC-FA/PTX) to cancer cells was much higher than micelles without folate (DOMC/PTX) or the commercially available injectable preparation of PTX (Taxol).Conclusion: Results indicate that the PTX-loaded DOMC-FA micelle is a successful anticancer-targeted drug-delivery system for effective cancer chemotherapy.Keywords: paclitaxel, folate, polymeric micelles, targeted delivery